Defeating Huanglongbing Pathogen Candidatus Liberibacter asiaticus With Indigenous Citrus Endophyte Bacillus subtilis L1-21 - Munir, Shahzad; Li, Yongmei; He, Pengbo; He, Pengfei; He, Pengjie; Cui, Wenyan; Wu, Yixin; Li, Xingyu; Li, Qi; Zhang, Sixiang; Xiong, Yangsu; Lu, Zhanjun; et al. (Frontiers in Plant Science, 2022)
Huanglongbing (HLB) has turned into a devastating botanical pandemic of citrus crops, caused by Candidatus Liberibacter asiaticus (CLas). Unfortunately, until now the disease has remained incurable with very limited control strategies available. Restoration of the affected microbial communities in the diseased host through introduction of an indigenous endophyte Bacillus subtilis L1-21 isolated from healthy citrus, may provide an innovative approach for the disease management. A novel half-leaf method was developed in vitro to test the efficacy of the endophyte L1-21 against CLas. Application of B. subtilis L1-21 at 104 cfu ml-1 resulted in a 1000-fold reduction in the CLas copies per gram of leaf midrib (107 to 104) in 4 days. In HLB-affected citrus orchards over a period of two years, the CLas incidence was reduced to <3% and the CLas copies declined from 109 to 104 g-1 of diseased leaf midribs in the endophyte L1-21 treated trees. Reduction in disease incidence may corroborate to a direct or indirect biocontrol effect of the endophytes as red fluorescent protein-labelled B. subtilis L1-21 colonized and shared niche (phloem) with CLas. This is the first large scale study for establishing a sustainable HLB control strategy through citrus endophytic microbiome restructuring using an indigenous endophyte.